Post-glacial uplift - Wojtal, Steven F. (Oberlin College Library, 1997)
The steep cliff resulted from erosion by waves along the ocean shore. This cliff is currently found several miles from the shoreline. It was eroded immediately following the melting of the ice cap and was later raised significantly above sea level by post-glacial rebound.